Internet of things. IoT infrastructures : first International Summit, IoT360 2014, Rome, Italy, October 27-28, 2014, Revised Selected Papers /: IoT infrastructures : first International Summit, IoT360 2014, Rome, Italy, October 27-28, 2014, Revised Selected Papers. Part II : (2015) - Unknown
No abstract available